Proposta de aplicações de teoria dos jogos no ensino médio - PAGANUCCI, Tarcísio de Castro (2018)
Game theory is a part of Maths that analyses interaction decisions among agents or rational players under strategic behaviour during a competition. This theory could be applied in many contexts, making modelling processes of various possible situations, such as fight for market, political competition, verdict decision by members of a jury, competition between people in public sale etc. In this paper, main concepts of Game Theory will brie y be under analyses involving static and dynamic games. Finally, some solved examples and suggestions will be presented to ensure application in high school.